2019
DOI: 10.1002/cssc.201802416
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Multicomponent Synthesis of Pyrroles through Acceptorless Dehydrogenation Hydrogen Autotransfer Catalysis: Experiment and Computation

Abstract: An ew base metal catalyzed sustainable multicomponent synthesis of pyrroles from readily available substrates is reported. The developed protocolu tilizes an air-and moisture-stable catalyst system and enablest he replacement of themutagenic ahaloketones with readily abundant 1,2-diols. Moreover,the presented method is catalytic in base and the sole byproducts of this transformation are water and hydrogen gas. Experimental and computationalm echanistic studies indicatet hat the reactiont akes place through ac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 80 publications
1
41
0
Order By: Relevance
“…As it has been previously reported in similar homogeneous catalysts, 16,28 proton transfer from the hydroxyl group in the alcohol to the N in the catalyst is hypothesised as a barrier-less process for the step-wise mechanism (see Fig. S1 at the ESI †).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…As it has been previously reported in similar homogeneous catalysts, 16,28 proton transfer from the hydroxyl group in the alcohol to the N in the catalyst is hypothesised as a barrier-less process for the step-wise mechanism (see Fig. S1 at the ESI †).…”
Section: Resultssupporting
confidence: 55%
“…16 Definitively, these are just a few instances amongst the plethora of organic transformations catalysed by manganese that have been reported in the last lustrum. [17][18][19][20][21][22][23][24][25][26] Encouraged by our interests in the unravelling of the mechanistic aspects in the catalytic chemistry of manganese, [27][28][29][30] the recent work by Milstein et al, 31 reporting for first-time a manganese-catalysed coupling of alcohols and hydrazone to form alkenes, caught our attention. As an alternative to the classical approaches for the synthesis of olefins from carbonyl compounds (such as Wittig, 32 Peterson, 33 or Julia 34 olefinations), Milstein and co-workers offer an unprecedented base-and waste-free procedure for the direct transformation of alcohols into alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a multi‐component synthesis of highly substituted pyrroles 33 via the ADC of 1,2‐diols 28 , ketones 20 , and primary amines 2 in the presence of lutidine derived pincer complex Mn‐30 , and a catalytic amount of KO t Bu was developed (Scheme ) . Mechanistic studies showed that reaction takes place through a combined ADC and BH methodology ( vide infra ).…”
Section: C−c/c−x/x−x Multiple Bond Formationsmentioning
confidence: 99%
“…A manganese‐pincer complex that catalysed the three‐component reaction of a 1,2‐diol, an α‐functionalised ketone, and a primary amine was introduced by same group for the synthesis of substituted pyrroles (Scheme ) . A stable manganese complex ( 105 ) is used with t‐ BuOK as base which generates the active catalyst and the reaction proceeds at 135 °C for 24 h. Various ketones, amines and diols worked well in this reaction protocol in which a bulky amine like adamantylamine and substituted as well as cyclic vicinal diols have lower reactivity.…”
Section: Synthesis and Derivatisation Of Heterocyclic Compoundsmentioning
confidence: 99%